Cost-Utility of Antimicrobial Prophylaxis for Treatment of Children With Vesicoureteral Reflux - Shaikh, Nader; Rajakumar, Vinod; Peterson, Caitlin G.; Gorski, Jillian; Ivanova, Anastasia; Gravens Muller, Lisa; Miyashita, Yosuke; Smith, Kenneth J.; Mattoo, Tej; Pohl, Hans G.; Mathews, Ranjiv; Greenfield, Saul P.; et al. (Frontiers in Pediatrics, 2020)
Objective: Antimicrobial prophylaxis for children with vesicoureteral reflux (VUR) reduces recurrences of urinary tract infection (UTI) but requires daily antimicrobials for extended periods. We used a cost-utility model to evaluate whether the benefits of antimicrobial prophylaxis outweigh its risks and, if so, to investigate whether the benefits and risks vary according to grade of VUR. Methods: We compared the cost per quality-adjusted life-year (QALY) gained in four treatment strategies in children aged <6 years diagnosed with VUR after a first UTI, considering these treatment strategies: (1) prophylaxis for all children with VUR, (2) prophylaxis for children with Grade III or Grade IV VUR, (3) prophylaxis for children with Grade IV VUR, and (4) no prophylaxis. Costs and effectiveness were estimated over the patient’s lifetime. We used $100,000/QALY gained as the threshold for considering a treatment strategy cost effective. Results: Based on current data and plausible ranges to account for data uncertainty, prophylaxis of children with Grades IV VUR costs $37,903 per QALY gained. Treating children with Grade III and Grade IV VUR costs an additional $302,024 per QALY gained. Treating children with all grades of VUR costs an additional $339,740 per QALY gained. Conclusions: Treating children with Grades I, II, and III VUR with long-term antimicrobial prophylaxis costs substantially more than interventions typically considered economically reasonable. Prophylaxis in children with Grade IV VUR is cost effective.